Two‐Dimensional Germanium Sulfide Nanosheets as an Ultra‐Stable and High Capacity Anode for Lithium Ion Batteries. Issue 29 (22nd November 2019) - Wang, Bo; Du, Wencheng; Yang, Yang; Zhang, Yufei; Zhang, Qi; Rui, Xianhong; Geng, Hongbo; Li, Cheng Chao
Abstract: Lithium ion batteries (LIBs) at present still suffer from low rate capability and poor cycle life during fast ion insertion/extraction processes. Searching for high‐capacity and stable anode materials is still an ongoing challenge. Herein, a facile strategy for the synthesis of ultrathin GeS2 nanosheets with the thickness of 1.1 nm is reported. When used as anodes for LIBs, the two‐dimensional (2D) structure can effectively increase the electrode/electrolyte interface area, facilitate the ion transport, and buffer the volume expansion. Benefiting from these merits, the as‐synthesized GeS2 nanosheets deliver high specific capacity (1335 mAh g −1 at 0.15 A g −1 ), extraordinary rate performance (337 mAh g −1 at 15 A g −1 ) and stable cycling performance (974 mAh g −1 after 200 cycles at 0.5 A g −1 ). Importantly, our fabricated Li‐ion full cells manifest an impressive specific capacity of 577 mAh g −1 after 50 cycles at 0.1 A g −1 and a high energy density of 361 Wh kg −1 at a power density of 346 W kg −1 . Furthermore, the electrochemical reaction mechanism is investigated by the means of ex‐situ high‐resolution transmission electron microscopy. These results suggest that GeS2 can use to be an alternative anode material and encourage more efforts to develop other high‐performance LIBs anodes. Abstract : Between the nanosheets : Two‐dimensional germanium sulfide nanosheets are synthesized by a controllable process, which could deliver superior lithium storage performance in terms of high specific capacity, stable cycling and good rate performances.